A systematic review of usability challenges and testing in mobile health - Al-Saadi, Tareq Ali; Aljarrah, Tamer Mohammed; Alhashemi, Anahed Mudheher; Hussain, Azham (Macrothink Institute, 2015)
Nowadays, the combining of advanced mobile communications and mobile account now in portable devices named "smart phones" has becomes more great uses.Among of these include health care professionals. Few studies in the challenge, blurred reality challenge facing the patient and developer alike in the usability of mobile health.Therefore, this paper